2020
DOI: 10.3390/ma13143084
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of Forming Railway Axles in 3- and 4-Roll Rolling Mills

Abstract: The paper presents a comparative analysis of skew rolling in 3- and 4-roll CNC rolling mills. The analysis is performed using the FEM-based commercial simulation software Simufact.Forming. The formation of both solid and hollow railway axles is analyzed. Distributions of effective strain, temperature and damage criterion in rolled axles are determined, and loads and torques acting on the tools during rolling are estimated. An innovative concept of calibrating hollow axles by the rotary compression tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…First, under the condition of meeting the existing railway gauge, the bearing area of the car body is relatively limited due to the relatively general width of the car body and the relatively small length of the car body, which is often easy to occur, so that the volume of goods carried by the car body rst seriously a ects the bearing capacity of the car body of railway at car [2]; secondly, because the total length of the car body is relatively limited, it can not meet the transportation requirements of large quantities and long goods. erefore, it is particularly important to strengthen the strength design of railway at car body [3,4]. Taking the strength calculation of the general at car body of a company as an example, this article compares di erent strength calculation methods and strength evaluation standards so as to deeply analyze the rationality of China's car body strength design code and provide a more scienti c and reliable theoretical basis for the structural strength design and analysis of railway at car surveying and mapping.…”
Section: Introductionmentioning
confidence: 99%
“…First, under the condition of meeting the existing railway gauge, the bearing area of the car body is relatively limited due to the relatively general width of the car body and the relatively small length of the car body, which is often easy to occur, so that the volume of goods carried by the car body rst seriously a ects the bearing capacity of the car body of railway at car [2]; secondly, because the total length of the car body is relatively limited, it can not meet the transportation requirements of large quantities and long goods. erefore, it is particularly important to strengthen the strength design of railway at car body [3,4]. Taking the strength calculation of the general at car body of a company as an example, this article compares di erent strength calculation methods and strength evaluation standards so as to deeply analyze the rationality of China's car body strength design code and provide a more scienti c and reliable theoretical basis for the structural strength design and analysis of railway at car surveying and mapping.…”
Section: Introductionmentioning
confidence: 99%
“…This results in small energy consumption of the manufacturing process as well as light construction of the rolling mill. The latest numerical analyses [16,17] indicated that this method would allow one to manufacture hollow rail axles.…”
Section: Introductionmentioning
confidence: 99%
“…
Tubes with variable wall thickness corresponded to their load distribution have advantages in weightsaving and resource-saving. Because of the advantages, those tubes are applied to bicycles frame and proposed to apply automotive driveshafts [1] and railway axles [2]. Those tubes should be tailormade to reduce their weight effectively; therefore, flexible forming is suitable for their production.
…”
mentioning
confidence: 99%